Plummer-Vinson syndrome - Suiffet, Walter R; Zerboni, Eugenio; Vega, Dardo (Cirugía del Uruguay, 2020)
In conjunction with a case, a survey is conducted of the syndrome of PlummerVinson, including the clinical, hematologic, radiologic and endoscopic aspects. An analysis of the pathogenic notions reveals the diversity of views in the production mechanism of this very peculiar condition, stress being laid on the significance of the hematologic dis, turbances as primary microcytic features. Hypochromic anemia, probably due to a disturbed iron metabolism and to avitaminosis are apparently the main causative factors. Diagnosis is based on an understanding of the syndrome and an investigation of its component,s. Treatment involves the replacement of the dificit elements as well as a permanent follow-up in view of the chronic course of the disease and its tendency toward remissions and exacerbations. Due consideration should be given to the likelihood of neoplastic transformation, a feature demanding a periodic control of those suffering this bizarre syndrome.